Дослідження динамічних характеристик мехатронних систем з гідравлічним приводом - Панченко, Анатолій Іванович; Панченко, Анатолий Иванович; Panchenko, Anatolii; Волошина, Анжела Анатоліївна; Волошина, Анжела Анатольевна; Voloshyna, Anzhela; Панченко, Ігор Анатолійович; Панченко, Игорь Анатольевич; Panchenko, Ihor; Волошин, А. А. (ТДАТУ, 2020)
UK: Дослідження динамічних процесів мехатронних систем з планетарними гідромоторами, з метою прогнозування зміни їх вихідних характеристик, є рішенням одним з актуальних завдань, пов'язаних з поліпшенням якості функціонування самохідної техніки. Обґрунтовано вихідні дані і початкові умови моделювання перехідних процесів, що відбуваються в мехатронный системі з планетарним гідромотором. Досліджено динаміку зміни вихідних характеристик мехатронної системи з серійним і модернізованим гідромоторами з урахуванням конструктивних особливостей системи роторів. Встановлено, що коливання діаметрального зазору в системі роторів серійного гідромотора викликає значні пульсації тиску і крутного моменту. При цьому, стабілізація діаметрального зазору в системі роторів модернізованого гідромотора дозволяє усунути пульсації тиску і крутного моменту на всьому протязі процесу розгону. RU: Исследование динамических процессов мехатронных систем с планетарными гидромоторами, с целью прогнозирования изменения их выходных характеристик, является решением одной из актуальных задач, связанных с улучшением качества функционирования самоходной техники. Обоснованы исходные данные и начальные условия моделирования переходных процессов, происходящих в мехатронной системе с планетарным гидромотором. Исследована динамика изменения выходных характеристик мехатронной системы с серийным и модернизированным гидромоторами с учетом конструктивных особенностей системы роторов. Установлено, что колебания диаметрального зазора в системе роторов серийного гидромотора вызывает значительные пульсации давления и крутящего момента. При этом, стабилизация диаметрального зазора в системе роторов модернизированного гидромотора позволяет устранить пульсации давления и крутящего момента на всем протяжении процесса разгона. EN: In hydraulic drives of mechatronic systems of self-propelled equipment, planetary hydraulic motors are widely used, similar to orbital and gerotor ones. The principle of their operation is based on the principle of operation of a planetary gearbox. The rotor system is one of the main units of the planetary hydraulic motor, which determines its performance. The design of the rotor system is based on the principle of operation of a toothed pair (movable and stationary rotor) with internal hypocycloidal gearing. Under the action of the hydraulic field, which acts as a crank of the planetary gear, the movable rotor rolls along the stationary one. Their disadvantage is the unevenness of the output characteristics, especially during transient processes, due to the error in the shape of the elements of the rotor system. The study of the dynamic processes of mechatronic systems with planetary hydraulic motors, in order to predict changes in their output characteristics, is a solution to one of the urgent problems associated with improving the quality of the functioning of self-propelled equipment. A structural and functional diagram of a dynamic model of a mechatronic system with a planetary hydraulic motor has been developed. The initial data and initial conditions for modeling transient processes occurring in a mechatronic system with a planetary hydraulic motor, as well as design parameters of the planetary hydraulic motor rotors system, affecting the change in its output characteristics, are substantiated. The dynamics of change in the output characteristics of a mechatronic system with serial and modernized hydraulic motors is investigated, taking into account the design features of the rotor system. It has been established that fluctuations in the diametral clearance in the rotor system of a serial hydraulic motor cause significant pressure and torque pulsations. At the same time, stabilization of the diametrical clearance in the rotor system of the modernized hydraulic motor allows eliminating pressure and torque pulsations throughout the research of the acceleration process. It was found that the size of the diametrical clearance in the rotor system does not affect the nature of the change in the flow rate of the working fluid and the shaft rotation frequency of the serial and modernized hydraulic motors.
Исследование динамических характеристик мехатронных систем с гидравлическим приводом
Research of dynamic characteristics of mechatronic systems with a hydraulic drive
Keywords: мехатронна система; планетарний гідромотор; вихідні характеристики; система роторів; динамічна модель; діаметральний зазор; мехатронная система; планетарный гидромотор; выходные характеристики; система роторов; динамическая модель; диаметральный зазор; mechatronic system; planetary hydraulic motor; output characteristics; rotor system; dynamic model; diametral clearance